The study of university teachers in contemporary history - Guereña, Jean-Louis (Historia y Memoria de la Educación, 2015)
Today we are justified in affirming that the world of the nineteenth and twentieth century Spanish university, and in particular its teachers, has become a fully consolidated subject of historiographic research. In particular, the prosopographical approach has become a comparatively common practice among researchers focusing on the study of the history of university teachers. In this regard, the ambitious, in-depth initiative undertaken in the preparation of the Diccionario de catedráticos españoles de Derecho (1847-1943) (Dictionary of Spanish Law Professors) was a milestone in the field. We will also focus on the continuing interest regarding the levels of hierarchy observed among full professors, and we will approach this issue from a sociological perspective that takes into account the body of professors as a whole. In truth, both the Dictionary of Spanish Law Professors and the study of hierarchies suffer from a «flaw» dating from their very conception, namely, that they only take into consideration the body of full professors. In doing so they exclude the «university women» (until 1953) as well as anyone who was not a full professor. Another «variable» that was not taken into consideration was the social background of the professors, alongside other aspects that could be considered to pertain to the «university condition». Thus our perspective goes beyond a purely «academic» history of the university, providing instead a «social» history of university professors. An undertaking as hefty as this can only be carried out in a collective, interdisciplinary fashion.